Profile of Mathematical Creative Thinking Ability of High School Students Reviewed from Cognitive Style - Hartati, Novani; Janudin, Agus; Yusuf, Yusfita (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2025)
Vocational school students have distinctive characteristics that are influenced by a variety of factors, including their social, cultural, and cognitive backgrounds. In the world of education, the development of creative thinking skills is an important aspect for vocational school students. However, each student's level of creativity varies, and one factor that contributes to this difference is cognitive style. This study aims to examine the influence of cognitive style on the mathematical creative thinking ability of high school students in Sumedang Regency. The method used is a qualitative approach with a descriptive design, where data is collected through mathematical creative thinking tests as well as semi-structured interviews. The study participants totaled 28 students, who were categorized based on their cognitive styles into Field-Independent (FI) and Field-Dependent (FD) groups. Data analysis was conducted through the process of reduction, presentation, and concluding, which revealed that students' cognitive style influenced their understanding and response to mathematical information. The results of the study revealed that students with FI's cognitive style tended to have higher creative thinking skills, able to solve problems with a more flexible and complex approach. In contrast, students with FD cognitive style have difficulty thinking flexibly and adapting to various methods, so their level of creativity in solving math problems is lower. This finding is expected to provide insight for educators in designing more effective learning strategies to encourage the development of student creativity in mathematics.